A Mild Synthesis of Bicyclic Alkoxyoxazolium Salts from Proline and Pipecolic Acid Derivatives. Issue 31 (8th August 2019) - Spinozzi, Eleonora; Bauer, Adriano; Maulide, Nuno
Abstract : A regio‐ and chemoselective preparation of bicyclic alkoxyoxazolium salts from amide derivatives of proline and pipecolic acid by electrophilic amide activation is reported. Mechanistic NMR experiments suggest an unusual role for the base and highlight the effect of substitution pattern of the substrates. Abstract : All about no base: A regio‐ and chemoselective preparation of bicyclic alkoxyoxazolium salts from amide derivatives of proline and pipecolic acid by electrophilic amide activation is reported. Mechanistic NMR experiments suggest an unusual role for the base and highlight the effect of substitution pattern of the substrates.